Influence of Drying–Wetting Cycles on the Water Retention and Microstructure of Residual Soil - Xu-tang Xu; Dao-qi Liu; Zhen-xing Xian; Feng Yang; Wen-bin Jian; Xiang Xu; Jian-bin Huang (Geofluids)
Due to frequent changes in the humid and hot environment, the residual soil with a particle-size distribution (PSD) from gravel to clay experiences multiple drying–wetting cycles. The pressure plate test and nuclear magnetic resonance (NMR) spectroscopy were used to investigate the influence of drying–wetting cycles on the soil–water characteristic curve (SWCC) and pore-size distribution (POSD) of undisturbed residual soil. The results showed that the water-holding capacity of the residual soil decreased as the number of drying–wetting cycles increased and gradually stablilized, and then the van Genuchten (VG) model was found to perform well on the SWCC during the drying–wetting processes. The NMR results indicated a double-pore structure, and the porosity of the residual soil as well as the internal water content increased smoothly with more drying–wetting cycles. The obtained POSD curve of soil implied that drying–wetting cycles had a more obvious effect on small pores and macro-pores than on micro-pores and meso-pores. Theoretical calculations evinced that the product of the matric suction and relaxation time should be constant at a constant temperature. However, the experimental results did not effectively reflect such a relation between the matric suction and relaxation time. A modified VG model based on the cumulative pore volume was utilized to describe the POSD under drying–wetting cycles. Subsequently, the proposed Rational2D surface equation was used to accurately reflect the internal relationship between the SWCC and POSD curve under different numbers of drying–wetting cycles. Moreover, the fractal model for the SWCC derived from the capillary theory confirmed that the matric suction had a strong linear relationship with the relative volumetric water content in the log-log scale. Also, the fractal dimension can be approximated as a constant, because its attenuation is small with more drying–wetting cycles.